Linguagem não verbal na interação em sala de aula de língua estrangeira - Dantas, Lílian Maria (2007)
The main objective of this research is to analyze the influence of nonverbal language (together with verbal) in EFL classroom interaction. Starting from the concept of language as a social activity and basing our studies in Discourse Analysis, Conversational Analysis and Interactional Sociolinguistics, I developed a micro analysis of discourse study which happened at the extension school of English from the Federal University of Alagoas. The corpus was defined by audio and video recordings and its transcriptions, interviews and questionnaires. Among many types of nonverbal language, I chose as the focus of our investigation the smile (EKMAN, 2003; PEASE and PEASE, 2005; CARVALHO, 1999; KINDE, 1999) because it showed out to be an important element to increase classroom interaction through a convivial strategy (used by the teacher as a balance between the instructional and the spontaneous discourse, based on KRAMSCH, 1987); to promote a funny learning environment through teacher and learners own experiences and to reprimand learners (exerting power and saving face) for not doing their homework. These three types of smile contributed to lower the affective filter, increase interaction and consequently improve students learning. In pedagogical terms, the classroom showed to be a place where teacher and students build up a learning and teaching culture and where the smile helped keep interaction high, developing a convivial environment which affected students learning positively.